Carbon flow in a sanitary landfill in Malaysia - Agamuthu, Pariatamby; Muda, M.A.; Venu Mahendra, M. (2011)
Jeram Sanitary Landfill (JSL) received 766,500 tonnes of municipal solid waste in 2010, from Kuala Lumpur and Selangor Municipality. Domestic waste, bulky waste, garden waste and domestic sewage sludge are generic classification of waste landfilled in JSL. Waste biomass, in JSL for example, paper, food and garden waste, wood and textiles, constitute 62 % of the MSW. We have attempted to quantify the C flow in a dynamic system i.e sanitary landfill in Malaysia via waste input- output analysis, C element flow and the total Substance Flow Analysis (SFA) of C. Mass balance of C was attempted using STAN software. In one-year of landfilling, 29% of the input of the organic C left the landfill via landfill gas pathway, while, less than 1% escaped via leachate pathway. In the same year, more than 70% of the organic C was still in the landfill as sink. Some biomass materials do not fully decompose and the C compound sequestered inside the landfill body and is not released into the atmosphere.